The effectiveness of postnatal gymnastics on reducing diastasis rectus abdominis and improving knowledge in postpartum women: A case study - Aisyah Aisyah; Eni Folendra Rosa; Lisdahayati Lisdahayati; Nelly Rustiati (Lentera Perawat, 2025)
Background: Diastasis rectus abdominis (DRA) is a common condition in postpartum women characterized by abdominal muscle separation, which may lead to functional disorders and reduced quality of life. One of the effective interventions is postpartum exercise, a simple physical activity designed to strengthen the abdominal muscles and accelerate recovery. Objective: This study aimed to describe the implementation of education and postpartum exercise to reduce DRA and increase knowledge among postpartum mothers. Methods: A descriptive case study design with a nursing care approach was applied to two multiparous postpartum mothers with DRA >2.5 cm. Interventions consisted of health education and postpartum exercise training conducted over seven consecutive days. Data were collected through interviews, observations, questionnaires, and DRA measurements using a simple caliper. Results: The findings showed a reduction in DRA size, from 2.96 cm to 2.78 cm in client I and from 2.86 cm to 2.64 cm in client II. Knowledge scores also increased significantly, with correct responses on the questionnaire improving from 4–5 to 10 out of 10 items. Conclusion: Education and postpartum exercise with a nursing care approach were proven to reduce DRA size and enhance maternal knowledge. Postpartum exercise can be recommended as a simple, cost-effective, and practical nursing intervention to support abdominal muscle recovery in postpartum mothers.